9x-2.1+.9=.2(5-x)

Simple and best practice solution for 9x-2.1+.9=.2(5-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-2.1+.9=.2(5-x) equation:


Simplifying
9x + -2.1 + 0.9 = 0.2(5 + -1x)

Reorder the terms:
-2.1 + 0.9 + 9x = 0.2(5 + -1x)

Combine like terms: -2.1 + 0.9 = -1.2
-1.2 + 9x = 0.2(5 + -1x)
-1.2 + 9x = (5 * 0.2 + -1x * 0.2)
-1.2 + 9x = (1 + -0.2x)

Solving
-1.2 + 9x = 1 + -0.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.2x' to each side of the equation.
-1.2 + 9x + 0.2x = 1 + -0.2x + 0.2x

Combine like terms: 9x + 0.2x = 9.2x
-1.2 + 9.2x = 1 + -0.2x + 0.2x

Combine like terms: -0.2x + 0.2x = 0.0
-1.2 + 9.2x = 1 + 0.0
-1.2 + 9.2x = 1

Add '1.2' to each side of the equation.
-1.2 + 1.2 + 9.2x = 1 + 1.2

Combine like terms: -1.2 + 1.2 = 0.0
0.0 + 9.2x = 1 + 1.2
9.2x = 1 + 1.2

Combine like terms: 1 + 1.2 = 2.2
9.2x = 2.2

Divide each side by '9.2'.
x = 0.2391304348

Simplifying
x = 0.2391304348

See similar equations:

| 9x+20y=-50 | | 4.4(n-5)+(-3n)=20 | | x+11=2*x+5 | | x+3x+1=7 | | x^2-2x=60+2x | | x+20=4x+2 | | (2x+3)(x-5)=4x+6 | | 2f-5=5f+22 | | 5=10+4.9x-4.9(x^2) | | x-23=71 | | y^2-6y+9=2y-10 | | 5x+10=4x+9 | | -3.4p+5.8-97p+0.40+5.8p= | | -p=-2p-2 | | 14/xy^2-1y2/8x^2 | | 5x^2+30x-60=0 | | 2x^2-480=0 | | m13/3 | | a=3a-8 | | 4(7)-3(6)/9= | | 3(y-1)=9-2(-7y-3) | | 40x^3-35x^2+8x-7= | | 2-5x=3x-5 | | 126=-16x^2+90x | | f(x)=x^2-10x-600 | | x^2-3+x=-21 | | 126=-16x^2+90t | | 430/x=.25 | | (5y-9)(1+y)=0 | | 1-7lnx=0 | | 5r-10=4r | | g(x)=x^2-10x-600 |

Equations solver categories